Variability of positioning and shape of the shoulder blade in man - Gerard-Białko, Danuta (Anthropological Review, 1984)
Observations on positioning and shape of the shoulder blade (scapula) were conducted on groups differing with respect to sex, age and occupation. As a criterion for shoulder blade positioning served localization of vertebral edges of scapulae, shape was determined using breadth-length ratio. It has been found that the most important changes in shoulder blade positioning ate related lo age, less importance lies with sex and profession. Shape of the shoulder blade seems to be related lo muscle development since in both sexes athletes have shape of the shoulder blade different from other persons.